PROSPECTS FOR THE DEVELOPMENT OF ECONOMIC RELATIONS OF AFRICA AND THE EUROPEAN UNION - P. Kamara; T. Titus; N. Sekongo (Вестник университета)
In article modern cooperation between the African countries and the EU, the main ways and forms of activization of development of economic euro-African cooperation, a condition and the factors promoting development of the European-African cooperation at the present stage are analyzed. The directions of diversification of forms, methods and mechanisms of the European-African cooperation are considered. The role of strategy of cooperation between the European Union and the international economic organizations in stabilization of economy of the African countries is analyzed. Special attention is paid to the perspective directions of development of economic cooperation of the countries of Africa and the EU. Authors called potential problems on the way of development of the international economic cooperation of the countries of Europe and Africa.